2017
DOI: 10.5090/kjtcs.2017.50.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Complications after Surgical Treatment of Thoracic Outlet Syndrome

Abstract: BackgroundSurgical treatment of thoracic outlet syndrome (TOS) is necessary when non-surgical treatments fail. Complications of surgical procedures vary from short-term post-surgical pain to permanent disability. The outcome of TOS surgery is affected by the visibility during the operation. In this study, we have compared the complications arising during the supraclavicular and the transaxillary approaches to determine the appropriate approach for TOS surgery.MethodsIn this study, 448 patients with symptoms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Pneumothorax after dissection low in the neck for vascular procedures is not uncommon and occurs frequently during operations for thoracic outlet syndrome using a supraclavicular incision. 5 In contradistinction to this case, rib resectionrelated pneumothorax is most often caused by direct pleural violation, which is often visualized during the course of the procedure. Other procedures involving dissection in the low neck similar to TCAR include carotid-subclavian bypass and subclavian transposition performed for a variety of indications.…”
Section: Discussionmentioning
confidence: 91%
“…Pneumothorax after dissection low in the neck for vascular procedures is not uncommon and occurs frequently during operations for thoracic outlet syndrome using a supraclavicular incision. 5 In contradistinction to this case, rib resectionrelated pneumothorax is most often caused by direct pleural violation, which is often visualized during the course of the procedure. Other procedures involving dissection in the low neck similar to TCAR include carotid-subclavian bypass and subclavian transposition performed for a variety of indications.…”
Section: Discussionmentioning
confidence: 91%
“…In a multi-institution database study, brachial plexus injuries were reported in 0.6% patients with nTOS following transaxillary first rib resection [50]. However, another study of transaxillary first rib resections in patients with nTOS reported a brachial plexus injury incidence of 9%, with an incidence of 4% after supraclavicular first rib resection [51].…”
Section: Surgical Management Strategy In Failed Conservative Managemementioning
confidence: 99%
“…A review of available literature did reveal a retrospective study specifically comparing complications of the transaxillary and supraclavicular approaches (n=102) [9]. They found no significant difference in the prevalence of pneumothorax, hemothorax, vascular injury, or plexus injury between the 2 approaches.…”
Section: Case Reportmentioning
confidence: 99%